Rancang Bangun Sistem Monitoring Kualitas Air Sungai Berbasis Aplikasi Smartphone - Latukolan, Gifford Jesaya; Wastumirad, Adi Widiatmoko (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Rivers have an important role in the lives of Indonesian people, as they function as resources that are used for various purposes. When rivers are utilized wisely and accompanied by awareness of protecting the environment, the water quality can be maintained properly. This study aims to monitor river water quality in the Pesanggrahan river basin. The river water samples are then analyzed using various water quality parameters so that the resulting data is expected to help the Indonesian people understand the condition and quality of river water and optimize efforts to protect the environment. In this research, the designed tool includes several sensors and other components. DS18B20 sensor is used to measure water temperature, analog pH meter sensor is used to measure pH levels, TDS meter sensor is used to measure water salinity, and analog turbidity sensor is used to measure water turbidity. In addition, the ESP32 wireless communication module and Arduino ATMega2560 microcontroller are used to process and transmit data generated by these sensors. This system can be monitored remotely through a smartphone using the internet of things through the Blynk application in real-time. In addition, the data can also be disseminated through Telegram Bot so that users can easily access and monitor water quality data through smartphones.